Institutional quality and economic growth: Empirical evidence from the Sudanese economy - Alexiou Constantinos; Tsaliki Persefoni; Osman Hashim Rasha (Ekonomski Anali, 2014)
This study aims to explore the extent to which conventional methods used in the majority of relevant growth studies can successfully interpret the economic performance of a highly underdeveloped African country such as Sudan. Applying an ARDL boundstesting approach to cointegration proposed by Pesaran et al. (2001), we look into the short-run as well as long-run relationships between institutional and various other key economic variables and economic growth over the period 1972-2008. The empirical results obtained suggest that, for the Sudanese economy, the quality of the institutional environment is one of the most important factors in defining economic prosperity.